Technical -Vocational Institute for the physically disabled: An examination of conflicting design requirements for people with mobility impairments. - Kyei-Dompim, Benjamin (2011)
A thesis submitted to the Department of Architecture,Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Architecture.